رسالة في رد المطلقة ثلاثا تأليف الشيخ جاعد بن خميس بن مبارك الخروصي (ت 1237 هـ) دراسة و تحقيق - الخليلي, عمر بن أحمد بن حمد (كلية العلوم الشرعية, 2025)
Keywords: Fiqh -- mariage

A critical analysis of the impact of early marriage on girls based on published autobiographies and a contemporary scholarly text – Īḍāḥ al-bayān fī nikāḥ al-ṣibyān - Mayberry, John F. (Medico-Legal Journal, 2025)
Background This work emerged from a need to better understand the “lived experience” of early marriage for girls and how it should impact on contemporary attitudes in the Muslim community and encourage it to support the international movement with the aim of a minimum common age of 18 years for marriage of young people. Objective To identify from contemporary published literature, including autobiographies and religious texts dealing specifically with early marriage, the effects of early marriage on individuals and to set this as a background to the extensive literature on its medical, psychological and social impact. Participants and setting: The setting is the published words of two women and a man who were involved in early marriages and a commentary on the topic by an Ibadi theologian. Methods The documents were identified through searching a range of databases using various search engines. Texts were then analysed for key terms describing the impact of early marriage and these were then grouped into themes. Findings The extracts raise questions linked to the issue of consent and the role of adult coercion, including physical force and threat of harm. In practice girls are given in marriage by their guardians against their wishes and international conventions on the rights and care of children, as well as that outlined in Qur’an 4 v6. Conclusion Modern Muslim states face a real challenge in implementing 18 as the minimum age for marriage, especially in how to manage opposition to appropriate new legislation from some traditionalist groups.
Keywords: Fiqh -- mariage

‏المنهاج في تذكرة الزواج - الصقري, إبراهيم بن سليمان (الموسعة قصصية, 2023)
Keywords: Fiqh -- mariage

وفاء : دليلك الشرعي إلى فقه التعامل مع الزوجات - الكندي, ماجد بن محمد (الصندوق الخيري للوقف العلمي ببهلا, 2019)
Keywords: Fiqh -- mariage

القواعد الأصولية و أثرها على اختلاف الفقهاء تطبيقاً على كتاب النكاح - باشعيب, وليد صالح (جامعة أم درمان الاسلامية, 2012)
Keywords: Fiqh -- mariage

الإيلاء: تعريفه، أركانه، شروطه، أحكامه - الخليلي, أحمد بن حمد (الكلمة الطيبة, 2021)
Marriage; annulment (Islamic law); divorce (Islamic law)
Keywords: Fiqh -- mariage

حياة زوجية سعيدة: من أجل حياة زوجية على النهج القرآني - خير الناس, نور الدين بن أحمد (Mzab Media, 2012)
Keywords: Fiqh -- mariage

المنهج في تذكرة الزواج - الصقري, إبراهيم بن سليمان (الموسعة قصصية, 2022)
Keywords: Fiqh -- mariage

فتاوي الزينة و الأعراس - الخليلي, أحمد بن حمد (مكتبة الجيل الواعد, 2014)
Keywords: Fiqh -- mariage

النكاح لدى اباضية المغرب: ‏القرن الثاني-القرن السادس هجري - الخليفي, حسين (دار آفاق للنشر, 2018)
تاريخيا تمتد هذه الدراسة من بداية القرن الثاني للهجرة ، تاريخ تسرّب المذهب الإباضي إلى إفريقية على يد الداعية سلمة بن سعد إلى أواسط القرن السادس للهجرة، تاريخ سقوط الدولة الصنهاجية ودخول قبائل بني هلال إلى إفريقية وهو تاريخ يتطابق كذلك مع بداية إنحصار الحركة الإباضية بإفريقية حيث سينجح المعز بن باديس في إستئصال المذاهب غير المالكية بما في ذلك المذهب الإباضي.
Keywords: Fiqh -- Ibadisme; Fiqh -- mariage

Le mahr (don nuptial) dans le droit islamique selon les écoles sunnites, chiites et ibadite - Farrouh, Ziyad (Ecole Pratique des Hautes Etudes, 2016)
Dans ce travail, une étude analytique comparative sur la notion du mahr (don nuptial) dans le droit islamique selon les différentes écoles juridiques est réalisée. Les écoles en question sont : ḥanafite, mālikite, šāfiʿite, ḥanbalite, imāmite, zaydite et ibāḍite. Tout d’abord, une présentation de la genèse de cette notion et aussi les difficultés de sa traduction est faite. A travers les enseignements de ces écoles, la notion de mahr et son importance dans le contrat de mariage sont analysées. Les points d’accords ainsi que ceux de divergences à travers une confrontation passionnante de sources classiques du fiqh sunnite, chiite et ibāḍite, sont ainsi développées. Cette recherche couvre la période entre Ier et VIIème siècle de l’hégire, ce qui correspond avec VIIème et XIVème siècle de l’ère chrétienne. L’aspect juridique du mahr, le montant, la nature et les différentes sortes de celui-ci sont des questions que nous allons tenter de répondre dans le présent travail. Nous traitons également des notions telles le mahr musamma ainsi que mahr al-miṯl. Cette étude à été réalisée en considérant le mahr dans toutes les situations juridiques : mariage, répudiation (ṭalāq), ẖulʿ et dissolution du mariage (fasẖ).
Keywords: Fiqh -- mariage

One or Three? Exploring the Scholarly Conflict over the Question of Triple riple Talāq (Divorce) in Islamic Law with Particular Emphasis on Oman - Azri, Khalid al- (Arab Law Quarterly, 2011)
This article explores Talāq, which refers to the right of men in Islam to divorce their wives, with particular emphasis upon triple Talāq. This article seeks to answer the question of how triple Talāq at one time is applied in modern-day Muslim societies, in light of contemporary socio-economic conditions. The historical events surrounding the emergence of triple Talāq in Islam demonstrates the possibility of its renewal in Islamic law. This is significant because it demonstrates that, contrary to the teaching of many Muslim scholars including contemporary Ibadī scholars in Oman, change and renewal are not inimical to Islam but rather intrinsic to it. I argue here that the inflexibility of Ibadī scholars regarding triple Talāq at one time promotes gender inequality and discriminatory practices in Oman, especially towards women. This article begins by exploring the different methods of Talāq in Islamic law. It then focuses on triple Talāq at one time (in one event). The discussion of triple Talāq at one time aims to explore the interaction between legal, economic and social factors, on one hand, and how these factors have affected the law of triple Talāq during both pre-modern and contemporary Muslim societies. Subsequently, the article will examine how contemporary Muslim scholars react to the new social and economic factors associated with triple Talāq at one time.
Keywords: Fiqh -- mariage